uitgewerkt

$
\eqalign{
  & f(x) = x \cdot \sqrt {x^2  - 1}   \cr
  & f'(x) = 1 \cdot \sqrt {x^2  - 1}  + x \cdot {1 \over {2\sqrt {x^2  - 1} }} \cdot 2x  \cr
  & f'(x) = \sqrt {x^2  - 1}  + {{x^2 } \over {\sqrt {x^2  - 1} }}  \cr
  & f'(x) = \sqrt {x^2  - 1}  \cdot {{\sqrt {x^2  - 1} } \over {\sqrt {x^2  - 1} }} + {{x^2 } \over {\sqrt {x^2  - 1} }}  \cr
  & f'(x) = {{x^2  - 1} \over {\sqrt {x^2  - 1} }} + {{x^2 } \over {\sqrt {x^2  - 1} }}  \cr
  & f'(x) = {{x^2  - 1 + x^2 } \over {\sqrt {x^2  - 1} }}  \cr
  & f'(x) = {{2x^2  - 1} \over {\sqrt {x^2  - 1} }} \cr}
$

©2004-2020 W.v.Ravenstein